ต้นทุนการให้บริการผู้ป่วยโรคไตเรื้อรัง โดยใช้ต้นทุนฐานกิจกรรมและเกณฑ์เวลา ของหน่วยไตเทียม โรงพยาบาลพุทธโสธร จังหวัดฉะเชิงเทรา - พูลเมืองรัตน์ สลินทร์นา; รุ่งเรืองวุฒิไกร นิภา; ยงวณิชย์ กฤติยา; เผ่าพันธ์ ณัฐสพันธ์ (Ph.D. in Social Sciences Journal, 2017)
การวิจัยครั้งนี้ มีวัตถุประสงค์ เพื่อวิเคราะห์ต้นทุนในการให้บริการผู้ป่วยโรคไตเรื้อรังของหน่วยไตเทียม โรงพยาบาลพุทธโสธร จังหวัดฉะเชิงเทรา โดยใช้วิธีต้นทุนฐานกิจกรรมและเกณฑ์เวลา (TDABC) ใช้การเก็บข้อมูลแบบย้อนหลัง และแบบไปข้างหน้า รวมถึงการสัมภาษณ์เชิงลึกกับผู้ปฏิบัติงาน ตั้งแต่ 1 กันยายน พ.ศ.2558 ถึง 31 ธันวาคม พ.ศ.2558 หลังจากนั้นทำการวิเคราะห์ข้อมูลโดยใช้สถิติเชิงพรรณนา ได้แก่ ค่าเฉลี่ยร้อยละ ผลจากการศึกษา พบว่า (1) ต้นทุนการให้บริการผู้ป่วยที่รักษาโรคไตเรื้อรังโดยการฟอกเลือดด้วยเครื่องไตเทียม (Hemodialysis–HD) ของหน่วยไตเทียม มีต้นทุนรวม (TDC) ต่อครั้งต่อผู้ป่วยหนึ่งรายเท่ากับ 2,394.85 บาท (ไม่รวมค่าตรวจเลือด) แบ่งเป็น ต้นทุนค่าแรง (LC) เท่ากับ 962.60 บาท คิดเป็นร้อยละ 40.19 ต้นทุนค่าวัสดุ (MC) เท่ากับ 1,207.32 บาท คิดเป็นร้อยละ 50.41 และต้นทุนค่าลงทุน (CC) เท่ากับ 224.93 บาท คิดเป็นร้อยละ 9.39 (2) การกำหนดเวลาที่ต้องใช้ พบว่า เวลาที่ต้องใช้ในการให้บริการผู้ป่วยหนึ่งรายใช้เวลารวมเท่ากับ 347.59 นาที แบ่งเป็น ส่วนที่ 1 กิจกรรมการเตรียมการก่อนและหลังการให้บริการเป็นเวลา 59.35 นาที ส่วนที่ 2 กิจกรรมที่ให้บริการต่อผู้ป่วยโดยตรงเป็นเวลา 288.24 นาที เวลาที่ใช้ในการให้การบริการผู้ป่วยมากที่สุดคือ การให้บริการของกลุ่มทรัพยากรพื้นที่ เท่ากับ 319.81 นาที รองลงมาคือ กลุ่มอุปกรณ์ครุภัณฑ์ เท่ากับ 297.10 นาที ลำดับที่สามคือกลุ่ม การให้บริการของกลุ่มการพยาบาล เท่ากับ 296.74 นาที (3) ต้นทุนทรัพยากรที่ไม่ได้นำมาใช้งาน (unused capacity) พบว่า ต้นทุนของทรัพยากรที่ไม่ได้นำมาใช้งานเรียงตามลำดับ ได้แก่ กลุ่มพื้นที่ ร้อยละ 67.43 กลุ่มคนงาน ร้อยละ 32.19 กลุ่มแพทย์ ร้อยละ 28.02 กลุ่มครุภัณฑ์ ร้อยละ 11.15 และกลุ่มพยาบาล ร้อยละ 5.71 ของเวลาที่ใช้ในการปฏิบัติงาน (practical time capacity) THE COST OF PROVIDING PATIENTS WITH CHRONIC KIDNEY DISEASE USING TIME DRIVEN ACTIVITY-BASED COSTING (TDABC) FOR HEMODIALYSIS UNIT BUDDHASOTHORN HOSPITAL CHACHOENGSAO PROVINCE In this thesis, the objective of this study is to analyze the costs of services rendered for the chronic kidney disease patients under study using the time-driven activity-based costing (TDABC) method and the retrospective study of data concerning costs. The prospective study method was applied to observing and timing the practical time capacity of service providers. In-depth interviews were conducted with practitioners from September 1 to December 31, 2015. Using techniques of descriptive statistics, the data collected were analyzed in terms of mean and percentage. Findings are as follows: 1. The costs of services rendered for chronic kidney disease patients using hemodialysis (HD) at the Hemodialysis Unit showed a time-driven costs (TDC) per time per single patient at 2,394.85 baht (exclusive of blood tests). This was divided into labor costs (LC) at 962.60 baht (40.19 percent); materials costs (MC) at 1,207.32 baht (50.41 percent); and capital costs (CC) at 224.93 baht (9.39 percent). 2. In determining the time spent, the researcher found that the time spent for providing services for a single patient was 347.59 minutes. This was divided into Part One: preparatory activities prior to and after the services rendered of 59.35 minutes and Part Two: activities in directly providing services to patients of 288.24 minutes. The time spent for patient services at the highest level were the services provided by the area capacity group (319.81 minutes). Next in descending order were the services rendered by the equipment and durable materials group (297.10 minutes) and the nursing group (296.74 minutes). 3. Concerning unused capacity, the following was found in descending order: the area group (67.43 percent); the laborers group (32.19 percent); the equipment and physicians group (28.02 percent); durable materials (11.15 percent); and the nursing group (5.71 percent) of the practical time capacity.